2004
DOI: 10.1074/jbc.m410323200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MAPKs and Their Possible MAPK Kinase Activators Involved in the Pto-mediated Defense Response of Tomato

Abstract: The Pto kinase mediates resistance to bacterial speck disease in tomato by activating host defenses upon recognition of Pseudomonas syringae pv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
96
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 40 publications
5
96
1
2
Order By: Relevance
“…LeMPK1/2/3 had been shown to function in host-specific AvrPto-dependent resistance to the bacterial pathogen P. syringae (28,45) and in Mi-1-mediated resistance to aphids (29). Our reduction-of-function study demonstrates that LeMPK1 and LeMPK2 are required for systemin-mediated resistance to M. sexta larvae.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…LeMPK1/2/3 had been shown to function in host-specific AvrPto-dependent resistance to the bacterial pathogen P. syringae (28,45) and in Mi-1-mediated resistance to aphids (29). Our reduction-of-function study demonstrates that LeMPK1 and LeMPK2 are required for systemin-mediated resistance to M. sexta larvae.…”
Section: Discussionmentioning
confidence: 75%
“…Both are activated by the same upstream MAPKKs, LeMKK2 and LeMKK4 (28). In addition, they are coordinately activated by wounding, systemin, oligosaccharide elicitors, UV-B radiation, and the fungal toxin fusicoccin (12,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditional expression of an active form of NtMEK2, which activates SIPK and WIPK, leads to HR-like cell death (Yang et al, 2001;Yoshioka et al, 2003). The same phenotype was observed in other plant species, including Arabidopsis and tomato (Ren et al, 2002;del Pozo et al, 2004;Pedley and Martin, 2004). Later, it was shown that activation of SIPK alone is sufficient to induce cell death Samuel and Ellis, 2002), and WIPK accelerates the cell death process .…”
mentioning
confidence: 82%
“…Biochemical studies from a number of laboratories demonstrated that SIPK and WIPK, two tobacco (Nicotiana spp.) MAPKs, and their orthologs in other plant species, including MPK6 and MPK3 in Arabidopsis (Arabidopsis thaliana), SIMK and SAMK in alfalfa (Medicago sativa), LeMPK1/2 (LeSIPK) and LeMPK3 (LeWIPK) in tomato (Lycopersicon esculentum), and PcMPK6 and PcMPK3 in parsley (Petroselinum crispum), are activated in cultured cells or plants treated with elicitors or after pathogen infection (Stratmann and Ryan, 1997;Zhang and Klessig, 1998a;Zhang et al, 1998Zhang et al, , 2000Romeis et al, 1999;Cardinale et al, 2000;Nü hse et al, 2000;Desikan et al, 2001;Lee et al, 2001Lee et al, , 2004Yuasa et al, 2001;Asai et al, 2002;Link et al, 2002;Ekengren et al, 2003;Holley et al, 2003;Kroj et al, 2003;del Pozo et al, 2004;Pedley and Martin, 2004). In tobacco, SIPK and WIPK share a common upstream MAPK kinase (MAPKK), NtMEK2 (Yang et al, 2001).…”
mentioning
confidence: 99%